Transplantation of Human Placenta-Derived Multipotent Stem Cells Reduces Ischemic Brain Injury in Adult Rats. Issue 3 (March 2015) - Wu, Kou-Jen; Yu, Seong-Jin; Chiang, Chia-Wen; Cho, Kuna-Hung; Lee, Yu-Wei; Yen, B. Linju; Kuo, Li-Wei; Wang, Yun
After the onset of stroke, a series of progressive and degenerative reactions, including inflammation, is activated, which leads to cell death. We recently reported that human placenta-derived multipotent stem cells (hPDMCs) process potent anti-inflammatory effects. In this study, we examined the protective effect of hPDMC transplants in a rodent model of stroke. Adult male Sprague–Dawley rats were anesthetized. hPDMCs labeled with a vital dye of fluorescing microparticles, DiI, or vehicle were transplanted into three cortical areas adjacent to the right middle cerebral artery (MCA). Five minutes after grafting, the right MCA was transiently occluded for 60 min. Stroke animals receiving hPDMCs showed a significant behavioral improvement and reduction in lesion volume examined by T2-weighted images 4 days poststroke. Brain tissues were collected 1 day later. Human-specific marker HuNu immunoreactivity and DiI fluorescence were found at the hPDMC graft sites, suggesting the survival of hPDMCs in host brain. Grafting of hPDMCs suppressed IBA1 immunoreactivity and deramification of IBA1+ cells in the perilesioned area, suggesting activation of microglia was attenuated by the transplants. Taken together, our data indicate that hPDMC transplantation reduced cortical lesions and behavioral deficits in adult stroke rats, and these cells could serve as a unique anti-inflammatory reservoir for the treatment of ischemic brain injury.